A Unidade Básica de Saúde como cenário para o ensino-aprendizagem do futuro médico: reflexões sobre a parceria ensino e serviço - Carvalho, Simone Bueno de Oliveira (2013)
Introduction: The Basic Health Care Unit (BHU) has shown a privileged setting of teaching to provide students the early experience and the knowledge of the social reality as well as the integration between the service and the community and therefore the experience of being a physician in a perspective of health social production and of civil rights, which may lead to some disruptures in the established processes that have already been historically constituted. Hence, the student may be an important interlocutor among the service, the university and the community, although such link may represent a considerable difficulty due to the relationship among the actors and the authors of that process. As far as it has been seven years of the curricular reform of the School of Medicine at Faculdade de Ciências Médicas e da Saúde da PUC-SP, it would be worth researching the current relationship among the health service institutions and the university. Objectives: This study aims to understand the perception of the faculty, the students and the professionals of these units of BHU and to envision possible ways to strengthen this relationship. Methods: This is a qualitative and quantitative study carried out with interviews among the key actors of the partnership of the teaching-medical service integration. The sample of the study has been intentionally selected from 14 faculties of FCMS, among them; four are also professionals of the BHU, 36 students in the 6th grade who graduated in 2011 and 38 professionals of six BHU that receive the students who have the experience to work in it. These employees answered a semi-structured questionnaire about the teaching-medical service integration and its evolution. The discursive responses have been analyzed using the technique of the Collective Subject Discourse and the responses to the closed questions have been analyzed according to the frequency distribution. The research project has been approved by the Ethics Committee of Local Research. Results: It has been found that 73.9% of the respondents, the majority of them are young men and women, have realized an improvement in the integration of teaching and medical service recently as "it is a forward and a backward way" as far as "it is a process," "a learning process that takes time". The opinions have expressed different interests among the actors, but the issues that involved the university service, structure of the units, universities and medical service integration, communication and planning have presented higher amplitude among the groups of participants. However the subjects with higher strength (frequency) and amplitude were the university involvement and communication. The Health-PET has been considered an important tool for the process of teaching- medical service integration